Types and frequencies of L2 learner’s errors: an error analysis - Nursyaheedah, Muhammad Isa; Hafizoah, Kassim; Fathiah Izzati, Mohammad Fadzillah; Nurkarimah, Yusof; Arulselvi, Uthayakumaran; Suriya Kumar, Sinnadurai; Nik Aloesnita, Nik Mohd Alwi (Universiti Malaysia Pahang, 2019)
The purpose of this study is to examine the types of language errors and discuss the most frequent errors committed by the international undergraduates from four different countries, Yemen, Sudan, People’s Republic of China and Somalia in written English essays. These students are enrolled in a mandatory English course at a local university in Malaysia. The Preparatory Intensive English (PIE) course is a specially catered language programme that requires students to achieve certain proficiency bands before joining the mainstream undergraduate engineering programmes. These students were tasked to write an essay on a topic of their interest and the error analysis from the essays showed that all of them made frequent language errors on the use of verbs, articles and prepositions (general grammatical errors), as well as errors in spelling, capitalisation, punctuation (substance errors), word choice (lexical errors), miscommunication of meaning (semantic errors), and sentence structure (syntactic errors). A total of 15 essay scripts written by the international students were collected. Error analysis was performed adhering to Corder’s (1967) method of error analysis. These errors analysis of the participants is further analysed following the error classifications suggested by Carl James (1998). The findings of the study implied that the explicit analysis of errors is useful to both the teaching instructors and intensive English course designers, in increasing the efficiency of the existing writing specifications in course modules. The further understanding of the different types of language errors will not only improve the instructor’s teaching and learning strategies in helping prospective students, but also will play a vital role in addressing similar language errors in the future.